Beyond general challenges: exploring physical education teachers' lived experiences and resilience in flexible learning environments - Jeric Quibral; Ma. Michelle Garganera; Glen Mangali (Universidade Estadual de Alagoas, 2024)
Resilience is the ability to bounce back from difficult situations and adapt to change. Resilience has become an essential skill for students, teachers, and institutions in the context of flexible learning during a pandemic. Unsurprisingly, there are several emotions, reactions, and feelings around the pandemic. During this phenomenon's transitional era, key institutions are experiencing discomfort and disorder. The primary objective of this study is to explore the lived experiences and resilience of physical education teachers during the implementation of the flexible learning approach. The study employed a phenomenological research approach and an inductive approach to develop theories or generalizations based on specific observations or data collected during the research process. The researchers developed a coping mechanism framework for physical education teachers that showed significant forces that distress their coping and adaptation. The study revealed that physical education teachers at Rizal Technological University were able to manage and adapt to the changeover because they embraced change, showed adaptability, and prioritized mental preparedness, collaboration, and administrative assistance. In addition, physical education teachers who increase their computer and technology literacy in preparation for flexible learning, reskilling, and upskilling play a crucial role in adjusting to the new norm. Edpuzzle, Padlet, and Wordwall, as well as other educational platforms, were found to aid educators in engaging their students in conversations. Similarly, social media sites were utilized as instructional resources and assessment instruments.